(untitled) (Baghdad Science Journal, 2024)
Risk factors for cardiovascular disease include obesity and Type 2 diabetes mellitus. The aim of this study is to evaluate Apelin-36 levels in Type2 diabetic(obese and non-obese) Iraqi patients ,finding out whether Apelin-36 is a future indicator of cardiovascular disease, and is an indicator of obesity or diabetes, or an indicator of both diseases ,when compared to obese control subjects without diabetes This study included 120 subjects:30 obese Diabetic type2 patients, 30 non-obese Diabetic Type2,60 as obese control group, adults between the ages from 30 to 65 years .The participants’ FBS, lipid profile (Cho ,Tri, HDL, LDL,and VLDL),HbA1C, Apelin-36 level, BMI , and waist-to-hip ratio were evaluated. Apelin-36 levels were significantly higher in obese Type 2 patients (27.68±0.67) than in non-obese patients (18.08±0.96) and obese control without diabetes individuals (10.23±0.29) (P<0.05). In comparison to obese type2 diabetic patients, obese control group ,non-obese type2 patients the BMI increased (p<0.05) (35.191±0.88, 32.05±0.35, 26.53±0.47). The mean values of Cho, tri, HDL, and VIDI do not differ significantly from those of the control groups. There is a significant difference in LDL levels between the obese patients and controls in the study’s participants (p<0.05).(Area Under the Curve) in the study = 0.980, indicating a perfect ROC test for correctly identifying individuals .Higher levels of Apelin-36 play an important role, which increases directly with obesity, resulting in an increase in the secretion of adipokines (Apelin-36) in the blood. Increasing BMI, lipid levels, and duration of the disease also contribute to the development of diabetes complications.